Enhanced survival of skeletal muscle myoblasts in response to overexpression of cold shock protein RBM3 - Ferry, Amy L. (American Physiological Society, 2011)
Cold-inducible RNA-binding protein (RBM3) is suggested to be involved in the regulation of skeletal muscle mass. Cell death pathways are implicated in the loss of muscle mass and therefore the role of RBM3 in muscle apoptosis in C(2)C(12) myoblasts was investigated in this study. RBM3 overexpression was induced by either cold shock (32°C exposure for 6 h) or transient transfection with a myc-tagged RBM3 expression vector. Cell death was induced by H(2)O(2) (1,000 μM) or staurosporine (StSp, 5 μM), and it was shown that cold shock and RBM3 transfection were associated with attenuation of morphological changes and an increase in cell viability compared with normal temperature or empty vector, respectively. No changes in proliferation were observed with either cold shock or RBM3 transfection. DNA fragmentation was not increased in response to H(2)O(2), and a cell permeability assay indicated that cell death in response to H(2)O(2) is more similar to necrosis than apoptosis. RBM3 overexpression reduced apoptosis and the collapse of the membrane potential in response to StSp. Moreover, the increase in caspase-3, -8, and -9 activities in response to StSp was returned to control levels with RBM3 overexpression. These results indicate that increased RBM3 expression decreases muscle cell necrosis as well as apoptosis and therefore RBM3 could potentially serve as an intervention for the loss of muscle cell viability during muscle atrophy and muscle diseases.